Cultural Routes and religious heritage: The multiple dynamics of a crossed category in a tourism context - Isabelle Brianso (Via@)
Since 1987, geographical traces (route, trail, via/way) of the Middle Ages have been transformed into Cultural Routes certified by the Council of Europe. These routes were once frequented by European travellers and pilgrims, but now attract a variety of walkers with diverse profiles (local inhabitants, pilgrim-walkers, tourist-ramblers) forming multiple communities with social, religious and heritage values. These communities of stakeholders operate in a tourism context via network-based dynamics, using participatory, socio-technical and digital tools to build their cultural, visual and European identity. They therefore play a central role in the recognition of this cultural object as a recent heritage category at the disciplinary crossroads of cultural geography, landscape and communication processes. This article examines a corpus of certified Cultural Routes with religious values using a qualitative methodology to classify them (typological approach) and analyse them (systemic approach).